Penerapan Model Pembelajaran Snowball Throwing Berbantuan Media Audio-Visual untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas V - Noviana, Irma; Maknun, Lukluil; Ahsani, Eva Luthfi Fakhru (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
This study aims to determine the improvement of learning outcomes through the application of snowball throwing learning model assisted by audio-visual media in grade V Indonesian language subjects at MI NU Tholibin This research uses Classroom Action Research method with descriptive qualitative method. The existence of changes in the learning model gives students increased enthusiasm for learning and student learning outcomes. This is evidenced by the data obtained by students in cycle I, namely the completeness of student learning outcomes in the low category with an average of 75 with a percentage of 60% because students are not used to using this learning model. In cycle II based on the data, student learning outcomes increased with an average of 85 and a percentage of 86%. This is because students are getting used to using the snowball throwing model assisted by audio visual media. So it can be concluded that through the application of the snowball throwing learning model assisted by audio-visual media can improve student learning outcomes in Class V Indonesian language subjects at MI NU Tholibin.